The law market - O'Hara, Erin A.; Ribstein, Larry E. (Oxford : Oxford University Press, 2009)
This text explores a new way of looking at law, not as something that can be changed only through cumbersome political and legislative processes or avoided by physical movement, but as something that can be shopped for in a market.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Venue -- United States; Forum shopping -- United States; Forum selection clause -- United States; Conflict of laws -- Jurisdiction -- United States; Domicile -- United States; Tax havens; International business enterprises -- Taxation -- United States; Income tax -- United States -- Foreign income